Anaplasia reflection in the future tense formation of the germanic languages - Bondarenko , Valeria; Botsman , Andriy; Dmytruk, Olha (Current issues of Ukrainian linguistics: theory and practice, 2022)
The purpose of this article is to separate grammatical structures that demonstrate the development of the future tense forms in the Germanic languages. The first step of research includes the identification of word forms for temporal description. Gradual identification of primitive analytical forms gives the possibility of tracing the gradual analytisation of the corresponding word combinations and their further transformation into stable analytical verb structures. Finding out latent features helps to recognize differentiated grammatical forms that are used to create and build the set of the formal Germanic future tense structures. The subject of the research is the components used to form temporal verb forms that project the action into the future. The Gothic language, which is understood as the initial, primary stage for the research, used forms of the present tense to describe the future action involving a phrase or an upper phrase context. Within the present tense forms a prefixal word-formation model was found. The Gothic optative was involved to render the future tense. The weak models of Gothic analytisation are connected with the infinitive phrase and auxiliary verb haban. Combination of auxiliary verbs with verbals (infinitive or participle I) were found in the North and West Germanic languages. These verb combinations involved a very restricted set of notional verbs used in two verbal forms. The first element of the phrase that falls under the process of future grammaticalization was preterite-present verbs, inchoative and some durative verbs. Stability of primary analytical temporal forms was created by using only two variants of verbals (infinitive or participle I). The first component of analytical temporal forms gradually lost its primary lexical meaning through its transformation into the auxiliary element. In the process of further differentiation of the Germanic languages some peculiarities were traced. The German language did not develop individual analytical forms with preterite-present (modal) verbs. Other West Germanic and Scandinavian languages used preterite-present (modal) verbs as a leading mechanism for temporal analytisation. Creation of analytical temporal forms happened within twofold formats.
Keywords: agenesia, analytical form, anaplasia, preterite-present verb, synthetic form, twofold format.